The strategic importance of the Republic of Serbia in China's Belt and Road Initiative - Dželetovič, Mitar; Garlick, Jeremy; Weinfurter, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The Belt and Road Initiative (BRI), led by China, is a vast infrastructure project involving over 150 countries and 30 international organisations, aiming to enhance connectivity between Asia, Europe, Africa, and South America. The BRI consists of a network of maritime routes and overland corridors, one of which traverses the Western Balkans. Except for Kosovo, all Western Balkan countries participate in the BRI, with Serbia seemingly standing out due to its intense partnership with China. This thesis examines why Serbia is the preferred partner of China within the BRI by comparing seven Western Balkan countries using criteria based on neoclassical realism theory.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses